Single aerosol trapping with an annular beam: improved particle localisation. - Dear, R; Burnham, DR; Summers, MD; McGloin, D; Ritchie, G (2012)
In this paper we explore the trapping of aerosol droplets using an annular beam, formed by blocking the central portion of a Gaussian beam, and quantify the improvements over conventional Gaussian beam traps. Recent work on the modelling of single aerosol dynamics within an optical tweezer trap [Burnham et al., Journal of the Optical Society of America B, 2011, 28, 2856-2864] has indicated that the use of annular beams can allow smaller droplets to be trapped, which we experimentally verify. We also demonstrate that annular beams allow droplets to be trapped at higher powers, and with reduced axial displacement with increasing power, than Gaussian beams. We confirm these results, due to a reduction in the axial scattering forces, using this theoretical model. Finally back focal plane interferometry is used to determine the axial and lateral trap stiffnesses for a series of droplets, showing a significant increase in the axial : lateral trap stiffness ratio from 0.79 ± 0.04 to 1.15 ± 0.04 when an annular beam is used.